EVALUASI MANAJEMEN ASET, ASURANSI DAN DANA PENSIUN BAPAK SUPRIYONO SEBAGAI KLIEN HNWI (HIGH NET WORTH INDIVIDUALS) - , Nefrida Elfitri ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aimed at how to manage a wealth of High Net Worth Individuals by knowing the client profile based on the type of risk-taking, analyzing and evaluating the management of wealth according to the needs of clients and 3 Pillar Wealth Management, and formulate alternative solutions and recommendations based on the type of client risk. This case study uses a client who is willing to provide information about the personal wealth of data, cash flow and some information related to the management of client assets. This type of risk based on the client questionnaire and the the authors make recommendations in accordance with client which is protection against a client wealth management, asset management and preparation of client pension fund. There are two alternative scenarios clients advice on wealth management. The results of the wealth management clients in scenario 1 can increase the client to Rp.886.960.186,00. Recommendations on the scenario 1 is health insurance Bringin Life Prospens and fire insurance ACA Asuransi, asset diversification (restaurants, boarding-lodging business, shop building, savings, deposits, fixed-income fund danamas mantap plus, ORI 005, mutual fund panin dana prima) and pension fund. The results of the wealth management clients in scenario 2 can increase the client to Rp.873.406.024,00. Recommendations on the scenario 2 is health insurance Manulife Pro Health and fire insurance Sinar Mas, asset diversification (laundry, boarding-lodging business, shop building, savings, deposits, fixed-income fund danamas mantap plus, ORI 005, mutual fund panin dana prima, mutual fund Panin Dana Maksima) and pension fund. Recommendations of the selected clients can improve cash flow net Rp. 880.043.116,00.